پرەنسیپی بەشداری گشتی وشەفافییەت لە پرۆسەی بنیادنانی دەستور: توێژینەوەیەکی بەراوردکارییە - Sarhang Hameed Barzanji; Ismail Azez Rahim (QALAAI ZANIST JOURNAL, 2019)
The process of constitution-making went through several stages; as it was initially appeared in the form of grant solely by the rules. However, this process became political elitism over time, culminating in setting constitution being as part of the changes towards democracy, and constitution-making became part of the peace-building process within societies. The principle of public participation and transparency has formed a cornerstone in the area of constitution-making; as they guarantee the success of the process and the balance between the unity of the homeland and peculiarities of the multiple and the various components of societies Thus, this process has two dimensions in terms of importance; one is a national dimension and the other is an international dimension, which is represented in the participation of the international community in the constitution-making process, especially in post-conflict states or the states that have just emerged from conflict. This international participation is just an embodiment of the principle of public participation and transparency in building national constitutions